Turkish folk medicinal plants, IX: Ovacik (Tunceli) [Türkiye'nin halk ilacı bitkileri, IX: Ovacık (Tunceli)] - DOĞAN, AHMET (Marmara University, 2010)
The aim of this study was made to reveal the plants used as traditional folk medicine in Ovaci{dotless}k (Tunceli). For this purpose, the field works have been done between May 2007-May 2008 in April, May, June and July lasting for 30 days, in total. During this research all the settlement centers (including 33 villages) have been visited, the specimens of the plants used as folk remedies have been collected and the information such as local names, ailments treated or therapeutic effects, plant parts used, method of administration, dosage, duration of treatment have been recorded. The collected plant specimens are kept in the Herbarium of the Faculty of Pharmacy, Marmara University (MARE). As a result of identification of 76 plant specimens, 67 species used as a traditional folk medicine, have been determined. Among them 65 species are wild and 2 species are cultivated plants. These plants and their local usage in treatment are presented in a table in the text. It was found out that the plants recorded in Ovaci{dotless}k are mostly used for cold, diabetes and wound.
Keywords: Folk medicine; Medicinal plants; Ovacik; Tunceli; Turkey